2004
DOI: 10.1177/147323000403200311
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Injection of Tenoxicam in Rats: Assessment of the Local Effects on the Articular Cartilage and Synovium

Abstract: This study investigated the possible local adverse effects of intra-articular administration of tenoxicam in the rat knee joint. A total of 50 rats were given 0.25 ml of a standard preparation of tenoxicam by injection into the right knee joint and 0.25 ml of 0.9% saline solution by injection into the left knee joint as a control. Groups of 10 rats were killed 24 h, 48 h, 7 days, 14 days and 21 days after tenoxicam administration. Two rats were sham operated; one was killed on the first day and the other on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…Control group showed no pathological changes whereas all of the samples which were applied tenoxicam have tissue loss and edema on days 1 and 2. There were no pathological changes in both groups on days 7, 14 and 21 [21]. The design and day 1 results of this study was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Control group showed no pathological changes whereas all of the samples which were applied tenoxicam have tissue loss and edema on days 1 and 2. There were no pathological changes in both groups on days 7, 14 and 21 [21]. The design and day 1 results of this study was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by OZYU-VACI et al, prominent changes in the joint surfaces of rats were observed 24 and 48 h after intra-articular application of tenoxicam, whereas no change was seen in the control group 22 . No changes were observed in the tenoxicam treated joints after 7, 14 or 21 days.…”
Section: Discussionmentioning
confidence: 97%
“…It is emphasized in the literature that the systemic and in vitro effects of NSAIDs have been extensively studied, but intraarticular administration has not been assessed adequately 22 . In a study by OZYU-VACI et al, prominent changes in the joint surfaces of rats were observed 24 and 48 h after intra-articular application of tenoxicam, whereas no change was seen in the control group 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ozyuvaci et al (14), tenoxicam was injected intraarticularly to the knee joints of 50 rats, which were then separated into groups of 10, and pathological changes in the joints were observed on days 2, 7, 14, and 21. No pathology was observed in the control group on days 1 and 2, while tissue loss and edema were observed in all rats treated with tenoxicam.…”
Section: Discussionmentioning
confidence: 99%